2023
DOI: 10.3390/healthcare11131853
|View full text |Cite
|
Sign up to set email alerts
|

School-Based Sleep Education Program for Children: A Cluster Randomized Controlled Trial

Abstract: Insufficient sleep contributes negatively to child developmental processes and neurocognitive abilities, which argues the need for implementing interventions to promote sleep health in children. In this study, we evaluated the effectiveness of a multimodal and multilevel school-based sleep education program in primary school children using a cluster randomized controlled design. Twelve schools were randomly assigned to either the sleep education or nonactive control groups. The sleep education group included a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…MAKINGtheLINK, an in-person intervention focused on increasing mental health literacy, did not result in statistically significant reductions in scores on a measure of depression and anxiety compared to a waitlist control, with small effect sizes ranging from d = 0.08 to d = 0.15 at six-weeks to twelve-month follow-ups (Lubman et al, 2020). One study examined Healthy Sleep, Health School Life, an in-person sleep education intervention, and found no statistically significant differences in parent-reported difficulties between participants in the intervention and no-treatment control group at a one-month follow-up, with a small effect size of d = -0.03 (Chen et al, 2023). In their study of a virtual-reality-based intervention, Shaw and Lubetzky (2021) found that scores on psychological stress decreased from baseline to post-intervention among the intervention group, but were not significantly different compared to the active control condition; the effect size was small, d = 0.05 (Shaw & Lubetzky, 2021).…”
Section: Interventions Targeting General Distress or Combined Problemsmentioning
confidence: 99%
“…MAKINGtheLINK, an in-person intervention focused on increasing mental health literacy, did not result in statistically significant reductions in scores on a measure of depression and anxiety compared to a waitlist control, with small effect sizes ranging from d = 0.08 to d = 0.15 at six-weeks to twelve-month follow-ups (Lubman et al, 2020). One study examined Healthy Sleep, Health School Life, an in-person sleep education intervention, and found no statistically significant differences in parent-reported difficulties between participants in the intervention and no-treatment control group at a one-month follow-up, with a small effect size of d = -0.03 (Chen et al, 2023). In their study of a virtual-reality-based intervention, Shaw and Lubetzky (2021) found that scores on psychological stress decreased from baseline to post-intervention among the intervention group, but were not significantly different compared to the active control condition; the effect size was small, d = 0.05 (Shaw & Lubetzky, 2021).…”
Section: Interventions Targeting General Distress or Combined Problemsmentioning
confidence: 99%